On-column refolding of recombinant fungal endoglucanase - Jamaluddin, Mohd Jamil Aizat; Mohd. Salleh, Hamzah (INSI Publications, 2012)
Endoglucanase is an industrially important enzyme involved synergistically in degradation of cellulosic materials into constitutive monomers with other cellulase enzymes. In this study, overexpression of (His)6-tagged endoglucanase from Fusarium oxysporum sp. in E. coli BL21(DE3) resulted to high tendency of endoglucanase in the form of inactive inclusion bodies when the host cells were cultured between at 37°C and induced by 0.20 mM (final concentration) IPTG. A simple and time-efficient on-column refolding scheme using immobilized metal-chelate affinity chromatography (IMAC) aided by AKTA purifier, an automated fast protein liquid chromatography (FPLC) system afforded highly purified refolded recombinant endoglucanase that was active in carboxymethyl cellulose (CMC) assay. The on-column refolding scheme is reliable and can be applied for efficient and robust method for lab-scale production of recombinant endoglucanase.